Sustainable Tourism Village Development Award-winning Indonesian Tourism Village 2021 (Studies Case in Sumberbulu Tourism Village) - Yohanes Sulistyadi; Rezka Aida PSPN (Budapest International Research and Critics University, 2022)
Village Tour Sourcefeather which is at in Village pendem Subdistrict Mojogedang Regency Karanganyar, Central Java Province, won 1st Place in the Best Tourism Village in the Souvenir Category in Indonesia Tourism Village Award Program 2021. With this achievement, Tourism Village Sumberbulu is one of the references for other regions that will develop destinations tour. So that souvenirs as wrong one characteristic special need developed by sustainable. Empress (2019) adds that development tourist sustainable that is development tourism that balances 3 aspects, namely economy, environment, and society. Type The research used is a qualitative research type, with the Grounded Theory method, and level explanation study descriptive. Technique collection data which used that is observation, Interview, document, and triangulation. Tool collector data in study this that is researcher that alone. Data processing procedures using the Miles and Model Huberman consisting of data reduction, data presentation, and data verification. Sumberbulu Tourism Village is included in the stage’s village tour develop which on moment this currently strive for development village tour sustainable so that it becomes an advanced tourist village, so it is necessary to provide assistance education and training for the local community. A tourism village development strategy that conducted consist from 3A, high school, and BASS. Attractions which offered that is attractions natural, culture, and artificial. Accessibility going to village tour already conducted repair with existence sign pointer direction and availability amenities which complete. On high school about HR and Public that is, training has been carried out for community groups with various kinds Skills. At BAS, tour packages have been prepared and marketing has been carried out by method follow various activity tourist. For increase system promotion which conducted namely by including various activities of the Sumberbulu Tourism Village into the agenda activity Tourist Province Java Middle so that could easier be known by traveler.